2016
DOI: 10.1017/s0144686x16000945
|View full text |Cite
|
Sign up to set email alerts
|

The meal as a performance: food and meal practices beyond health and nutrition

Abstract: The proportion of elderly people in the population is increasing, presenting a number of new challenges in society. The purpose of this qualitative study was to investigate how elderly persons with motoric eating difficulties perceive and perform their food and meal practices in everyday life. By using Goffman's concept of performance as a theoretical framework together with Bourdieu's thinking on habitus, a deeper understanding of food and meal practices is obtained. Semistructured interviews were conducted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 51 publications
1
11
1
Order By: Relevance
“…Eating difficulties are complex and consist of a variety of problems related to the process of eating from the pre-oral phase to the handling of food in the mouth and swallowing, affecting total energy and nutrient consumption. Eating difficulties are a major risk factor for malnutrition among older people [42]. In this study, malnutrition status in EI was higher than that reported in the non-institutionalized elderly [43].…”
Section: Nutritional Indicators Of Elderlycontrasting
confidence: 56%
“…Eating difficulties are complex and consist of a variety of problems related to the process of eating from the pre-oral phase to the handling of food in the mouth and swallowing, affecting total energy and nutrient consumption. Eating difficulties are a major risk factor for malnutrition among older people [42]. In this study, malnutrition status in EI was higher than that reported in the non-institutionalized elderly [43].…”
Section: Nutritional Indicators Of Elderlycontrasting
confidence: 56%
“…(Shune & Linville, 2019, p. 148) participants' feelings of "guilt and selfishness" (p. 616) as family mealtimes were no longer enjoyable for people with dysphagia. Nyberg et al (2018) also reported that participants believed their mealtimes were "not performed in a culturally proper way" (p. 93) and that they tried to maintain normality and inclusion by choosing regular foods that they could eat. LaDonna et al ( 2016) described similar coping strategies to overcome isolation, for example, by choosing meals that the person with dysphagia could share with friends and family (see further examples in Table 2).…”
Section: Attempts To Maintain Quality Of Lifementioning
confidence: 99%
“…(a) Personal attempts to maintain quality of life(b) Eating regular food(1) Characteristics of the individual and(2) overall quality of life (a)Klinke et al (2013),Klugman & Ross (2002),Luchesi & Silveira (2018),Milte et al (2017),Moloney & Walshe (2018),Nyberg et al (2018),Perry & McLaren (2003),Pontes et al (2017),Seshadri et al (2018),Shune & Linville (2019), and Tarlarini et al (2019) (b) Hellden et al (2018), Johansson & Johansson (2009), Klinke et al (2013), LaDonna et al (2016), Martino et al (2010), Milte et al (2017), Moloney & Walshe (2018), Perry & McLaren (2003), Seshadri et al (2018), and Shune & Linville (2019) Biopsychosocial impacts (a) Fatigue and sleep effects (b) Increased time to eat (c) Negative mental health impacts (d) Reduced desire to eat (e) Associated risk factors to dysphagia (1) Characteristics of the individual, (2) biological function, (3) symptoms, (4) functional health status, and (5) general health perceptions (a) Arslan et al (2019); Balandin et al (2009); de Faria Gaspar et al (2015); Gustafsson & Theorell (1995); Klinke et al (2013); Medin, Larson, et al (2010); Medin, Windahl, et al (2010); Miller et al (2006); Paris et al (2013); Printza et al (2020); Wegner et al (2018); and Yi et al (2019) (b) Balandin et al (2009), de Faria Gaspar et al (2015), Martino et al (2010), Printza et al (2020), Remijn et al (2019), Song et al (2020), Wegner et al (2018), and Yi et al (2019) (c) Balandin et al (2009), Carneiro et al (2013), de Faria Gaspar et al (2015), Ekberg et al (2002), Farri et al (2007), Gustafsson & Theorell (1995), Hewett et al (2016), Johansson & Johansson (2009), Klinke et al (2013), Klugman & Ross (2002), Manor et al (2018), Martino et al (2010), Moloney & Walshe (2018), Morisaki (2017), Pierce et al (2016), Plowman-Prine et al (2009), Printza et al (2020), Roy et al (2007), Tibbling & Gustafsson (1991), Turley & Cohen (2009), and Verdonschot et al (2013, 2016, 2017) (d) Alali et al (2018); Balandin et al (2009); da Costa Franceschini & Mourao (2015); Ekberg et al (2002); Farri et al (2007); Klinke et al (2013); Leow et al (2010); Medin, Larson, et al (2010); Miller et al (2006); Moloney & Walshe (2018); Paris et al (2013); Pitts et al (2019); and Remijn et al (2019) (e) Balandin et al (2009), Byeon (2019), Klinke et al (2013), Leow et al (2010), McAuliffe et al (2017), Pierce et al (2016), and Yi et al Characteristics of the individual, (2) biological function, (3) symptoms, (4) functional health status, and (5) overall quality of life (a) Balandin et al (2009); Carlsson et al (2004); Ekberg et al (2002); Jacobsson et al (2000); Klinke et al (2013); Manor et al (2018); Martino et al (2010); Medin, Larson, et al (2010); and Moloney & Walshe (2018) (b) Alali et al (2018), Balandin et al (2009), Klinke et al (2013), Martino et al (2010), and Moloney & Walshe (2018) (c) Ang et al (2019); Balandin et al (2009); Jacobsson et al (2000); Klinke et al (2013, 2014); Luchesi & Silveira (2018); Martino et al (2010); Medin, Larson, et al (2010); Medin, Windahl, et al (2010); Moloney & Walshe (2018); Remijn et al (2019); and Shune & Linville (2019) (d) Balandin et al (2009), Klinke et al (2013), Perry & McLaren (2003), and Roy et al (2007) (e) Balandin et al (200...…”
mentioning
confidence: 99%
“…It is interesting to note that the elderly people preferred being served food that was already plated, while the staff suggested that buffet serving was popular. The difference between the two focus groups results may be caused by the fact that the elderly people may sometimes find it hard to serve themselves due to tremor or weakness ( 45 ), while the staff may like to increase the independence of the elderly people and allow them to make independent choices. A more family-like situation may be possible if the staff were to eat together with the elderly people, as pointed out in the focus group with care staff.…”
Section: Discussionmentioning
confidence: 99%